Evaluating Animal Welfare Awareness and Practices Among Halal Slaughterers and Slaughterhouse Personnel in Malang Raya, Indonesia - Herawati; Ani Setianingrum (Postgraduate, University of Mataram, 2025)
Implementing animal welfare principles is essential for minimizing animal suffering and improving meat quality. Verifying the appropriateness of the slaughtering process is the halal slaughterer's responsibility. This study assessed the knowledge, attitude, and practices (KAP) of slaughterhouse personnel and halal slaughterers (JULEHA) in Malang Raya, East Java, Indonesia. A cross-sectional study used thirty-six closed-ended structural questionnaires, comprising six demographic questions and 10 questions for each knowledge-attitude-practice variables, with 50 respondents. Demographic data was analyzed descriptively, the correlation among demographic variables was analyzed using Spearman's test, and the correlation between KAP was analyzed using Pearson's test and path analysis. Study results showed the overall scores were high, knowledge (4.56, out of 5), attitude (4.13, out of 5), and practice (4.43, out of 5). Significant relationship between Certification and Occupation (ρ=0.32, p=0.026), Training and Occupation (ρ=-0.40, p=0.004), Training and Certification (ρ=-0.72, p<0.001), Attitude and Age (ρ=-0.45, p=0.001), Knowledge and Age (ρ=-0.33, p=0.018). A positive direct association of knowledge toward practice (β=0.68, p<0.001), attitude toward practice (β=0.23, p<0.016), and between knowledge and attitude (β=0.50, p<0.001). Regular training and continuing education are important to ensure animal welfare and produce safe, healthy, intact, and halal meat.